PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA STKIP PGRI SITUBONDO ANGKATAN 2022 - Efendi, M.Ridho’i; Dassucik, Dassucik; Rasyidi, Ahmad Hafas (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to determine the influence of entrepreneurial knowledge and entrepreneurial motivation on the entrepreneurial interest of STKIP PGRI Situbondo students in the 2022 cohort. The high unemployment rate in Indonesia serves as the primary backdrop for the importance of encouraging the younger generation, particularly students, to develop an interest and ability in entrepreneurship. Entrepreneurship knowledge and entrepreneurial motivation are believed to be internal factors that can influence such interest. This study employs a quantitative approach using the ex post facto method. The research sample consisted of 100 students selected through proportional random sampling from three study programs, namely Economics Education, Mathematics Education, and Information Technology Education. Data collection was conducted through questionnaires and documentation. Data analysis techniques included validity and reliability tests and chi-square tests. Based on the results of the simultaneous multiple linear regression test (F-test), based on the results of the table above, it can be concluded that the calculated F-value is 1827.369 and sig. 0.001, indicating that the significance level is 0.001 < 0.05, thus rejecting H0. Therefore, Ha is accepted, and it can be concluded that there is an influence of entrepreneurial knowledge and entrepreneurial motivation on the entrepreneurial interest of students.